Source of The Reservation in Relation to Increase Volume of Room Sales on Discovery Kartika Plaza Hotel - Ni Luh Novi Suryantini Dewi; I Gusti Agung Mas Krisna Komala Sari; I Nyoman Winia (EDUTOURISM Journal Of Tourism Research, 2020)
Discovery Kartika Plaza Hotel establishing cooperation with several source of reservations such as online travel agents, offline travel agents, free independent travelers (FIT) and groups in increasing volume room sales to win the competition between 5-stars hotels in Kuta. Data obtained through observation, interviews, library research and documentation. Data analysis is performed by quantitative analysis of secondary data, such as tests; partial correlation analysis, multiple correlation analysis, classic assumption test, multiple linear regression test, hypothesis test analysis, multiple determination coefficients, standardized coefficient beta statistical analysis, and effective contribution with the help of SPSS version 23. Based on the results of the analysis, partially there is a significant influence positive and significant between online travel agents for room sales volume with p-value 0.000 <0.05, offline travel agent for room sales volume with p-value 0.000 <0.05, FIT for room sales volume with p-value 0.000 <0.05 and group for volume room sales with p-value 0,000 <0.05. Also, online travel agents, offline travel agents, FIT and groups have a positive and simultaneous effect on room sales volume with p-value 0,000 <0.5 and total value of effective contributions of 99.2%. The most dominant variable is the offline travel agent with an Effective Contribution value of 45.83%.